(untitled) (Journal of Management and Social Sciences, 2023)
This article examined the discordant beliefs among Islamic sects in Northwest Nigeria on the second coming of Prophet ‘Iisa (Jesus), within the context of Hadeeth as a primary source of Islamic law; respecting the companions of Prophet Muhammad (SAW); abiding by the governance of secular political rulers and using Shaykhs (past pious spiritual leaders) as intermediaries to attain spirituality from Allah. It then investigated how each sect reacts when confronted with rivalry or aggression from another sect(s). Focus Group Discussions (FGDs) was used to collect data from male and female members of four purposively selected sects in Katsina, Kaduna and Kano States. Findings were analysed using thematic, narrative and textual explication approaches. Findings indicate that discordant beliefs within the context of believing in the second coming of Prophet ‘Iisa (Jesus), using Hadeeth as an Islamic source of legislation, respecting the Prophet’s companions, and abiding by secular leaders’ rules exist among the sects. While some of the discordant beliefs among them led to verbal insults and confrontations, some were managed and handled with calmness, wisdom and avoidance of potential conflicts, thereby averting any potential combative/physical intra-religious and inter-sectarian violent conflicts that may arise from discordant beliefs among the sects. The study concludes that although there were discordant beliefs among the four Islamic sects, they were able to manage their discordance through strategic conflict avoidance techniques. Therefore, we recommend that members of different Islamic sects in Northwest Nigeria find time to enroll themselves in formal education where they can seek knowledge for self-development and intellectual growth instead of relying only on the interpretations of their leaders on religious matters.